Economics Theory Through Applications - Cooper, Russell; John, Andrew (Open textbook library., 2012)
Russell Cooper and Andrew John have written an economics text aimed directly at students from its very inception. You're thinking, ”Yeah, sure. I've heard that before.“ This textbook, Economics: Theory Through Applications, centers around student needs and expectations through two premises: … Students are motivated to study economics if they see that it relates to their own lives. … Students learn best from an inductive approach, in which they are first confronted with a problem, and then led through the process of solving that problem. Many books claim to present economics in a way that is digestible for students; Russell and Andrew have truly created one from scratch. This textbook will assist you in increasing students' economic literacy both by developing their aptitude for economic thinking and by presenting key insights about economics that every educated individual should know. How? Russell and Andrew have done three things in this text to accomplish that goal: Applications Ahead of Theory: They present all the theory that is standard in Principles books. But by beginning with applications, students get to learn why this theory is needed. Learning through Repetition: Important tools appear over and over again, allowing students to learn from repetition and to see how one framework can be useful in many different contexts. A Student's Table of Contents vs. An Instructor's Table of Contents: There is no further proof that Russell and Andrew have created a book aimed specifically at educating students about economics than their two tables of contents.